-3k-1=12

Simple and best practice solution for -3k-1=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3k-1=12 equation:


Simplifying
-3k + -1 = 12

Reorder the terms:
-1 + -3k = 12

Solving
-1 + -3k = 12

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -3k = 12 + 1

Combine like terms: -1 + 1 = 0
0 + -3k = 12 + 1
-3k = 12 + 1

Combine like terms: 12 + 1 = 13
-3k = 13

Divide each side by '-3'.
k = -4.333333333

Simplifying
k = -4.333333333

See similar equations:

| x=3y(y+w)-1 | | k=5/8m | | 4x-9+2x=-6x+5 | | 6(3x+2)+5(7x-6)-12x=6(x-3)+5(6x-1) | | X^2-8x=100 | | 7xy+2y^2=1 | | 20y^4+35y^3+15y^2= | | 78-u=271 | | -1(t^2-3t-10)=0 | | -1=5-2x/3 | | x-23=x+77 | | -98/-18 | | (-8-90)/2(-8)-2 | | (-8-90)/2x(-8)-2 | | 4m^2-36mn+81n^2= | | x+4.9=6.89 | | 2.6x-52=1.3x | | 2.6x-52=1.3 | | 5x-27=x+30 | | 8ab^2-12a^2b= | | 2(y+x)=-(-3x+10) | | 29-35=-5 | | 8x-20=2x+40 | | 4x-7=-x-9 | | a^2+11=3a | | x^2+y^2+16x-12y+10=0 | | x^2+20x-74=8x-10 | | 3x^2-5-4x=10x+65-3x | | 6x+1=-0.4x-2 | | (x+y)(x+2y)= | | 3(2-x)-2(2x+1)=3 | | 6x+1=0.4x+2 |

Equations solver categories